An approach based on mean shift and KALMAN filter for target tracking under occlusion - Jie Zhao; Wen Qiao; Guo-Zun Men (2009 International Conference on Machine Learning and Cybernetics, 2009)
This paper combines the mean shift algorithm with the Kalman filer for target tracking. First, the starting position of mean shift is found by the Kalman filter, then the mean shift uses it to track the object position. The occlusion problem is a difficult problem during target tracking. When severe occlusion problem takes place, a novel method is proposed to solve this problem in this paper. In that case, the predictive position of the Kalman filter is regarded as its measured value. Make the Kalman filter has the ability to estimate the coming state. Then using the mean shift algorithm find the accurate target position in current frame. Experimental results show that the proposed algorithm is very effective to solve the occlusion problem.